HPLC Determination of Satranidazole in Rat Plasma - Jagtap, Onkar; Godse, Vijaya; Deshpande, Sangeeta; Deodhar, Meenakshi (Asian Journal of Chemistry, 2011)
A rapid, simple and sensitive RP-HPLC method with diode array detection (DAD) was developed for determination of satranidazole from rat plasma. Separation was achieved on reverse phase C18 column (250 mm × 4.6 mm × 5 μm), using a mixture of methanol: 10 mM phosphate buffer pH 3 adjusted with orthophosphoric acid, in ratio of 30:70 (% v/v) at a flow rate of 1 mL/min with UV detection at 320 nm within 10 min. The plasma samples were prepared by simple single-step deproteinization with acetonitrile, yielding more than 80 % extraction recovery. The calibration curve was linear (correlation coefficient of 0.9968) in the concentration range of 1-60 μg/mL. The lowest limit of quantification (LLOQ) was 1 μg/mL. The intra-day precision was less than 15 % RSD. The present method was selective enough to analyze satranidazole in rat plasma and was successfully applied for estimating the pharmacokinetic parameters of satranidazole following oral administration of single 54 mg/kg satranidazole to rats.